Role of lactic acid on cognitive functions - Coco, M.; Di Corrado, D.; Ramaci, T.; Di Nuovo, S.; Perciavalle, V.; Puglisi, A.; Cavallari, P.; Bellomo, M.; Buscemi, A. (The Physician and Sportsmedicine, 2019)
Objectives: The aim of this research was to establish cognitive changes in relation to blood lactate levels obtained during slow performance of a regimen of exercise sessions.